68.5k views
23 votes
3x - 2(6 - x) = 7x + 2(5 + x) - 6
What is the answer

User N S
by
5.9k points

2 Answers

10 votes

Answer: x = -4

Explanation:

first, we remove the parentheses.

3x - 12 + 2x = 7x + 10 + 2x - 6

then, we cancel equal terms.

3x - 12 = 7x + 10 - 6

then, we calculate.

3x - 12 = 7x + 4

next, we move the terms.

3x - 7x = 4 + 12

then, we collect like terms and calculate.

-4x = 16

finally, we divide both sides.

x = -4

User Bilabila
by
5.9k points
1 vote

Answer:

x= -4

Explanation:

User GrayFullBuster
by
6.4k points